Synthesis of undecagold cluster molecules as biochemical labeling reagents. 1. Monoacyl and mono[N-(succinimidooxy)succinyl] undecagold clusters - Reardon, J E; Frey, P A (Biochemistry (Easton), 1984)
This paper describes the synthesis and characterization of succinyl, phthalyl, and N-(succinimidooxy)-succinyl derivatives of the undecagold cluster complex tricyanoheptakis[4,4',4"-phosphinidynetris(benzenemethana mine)]undecagold, 1, molecular formula Au11(CN)3[P(C6-H4CH2NH2)3]7. These are useful as electron-dense reagents for labeling biological structures in preparation for electron microscopic analysis. Limited reaction of 1 with succinic or phthalic anhydrides produces a mixture of mono-, bis-, etc. (N-succinyl)-1 or (N-phthalyl)-1, which can be separated by anion-exchange chromatography at pH 11.5. Yields of monoacylated derivatives can be maximized by controlling the ratio of succinic or phthalic anhydride to 1. The remaining 20 primary amino groups can be dialkylated or acetylated, blocking their participation in further chemical modifications of the carboxylic functional group introduced in the succinylation or phthalylation of 1. These carboxyl groups can be activated as N-hydroxysuccinimido esters, which are acylating derivatives of 1. An example is mono[N-(succinimidooxy)-succinyl]icosa(N,N-dimethyl)-1 whose synthesis is described. Bis- and tris(N-succinyl) and -(N-phthalyl) derivatives of 1 are also produced and isolated in usable quantities.